DOCSISTM cable modem technology. - Fellows, D. (IEEE Communications magazine)
An overview of the cable modem interface standard is presented. This standard is the foundation for high-speed access to content on the Internet being offend by North American cable operators. It also facilitates retail sales of modems and integration into computers, is being adopted by international operators, and provides a path for convergence of video, data, and voice services on a broadband cable system. The details of the protocol stack and evolution of the standard are discussed